Synergism of Cattle and Bison Inoculum on Ruminal Fermentation and Select Bacterial Communities in an Artificial Rumen (Rusitec) Fed a Barley Straw Based Diet - Oss, Daniela B.; Ribeiro, Gabriel O.; Marcondes, Marcos I.; Yang, WenZhu; Beauchemin, Karen A.; Forster, Robert J.; McAllister, Tim A. (Frontiers in Microbiology, 2016)
This study evaluated the effect of increasing the proportion of bison relative to cattle inoculum on fermentation and microbial populations within an artificial rumen (Rusitec). The experiment was a completely randomized design with a factorial treatment structure (proportion cattle:bison inoculum; 0:100, 33:67, 67:33 and 100:0) replicated in two Rusitec apparatuses (n=8 fermenters). The experiment was 15 d with 8 d of adaptation and 7 d of sampling. Fermenters were fed a diet of 70:30 barley straw:concentrate (DM basis). True digestibility of DM was determined after 48 h of incubation from d 13-15, and daily ammonia (NH3) and volatile fatty acid (VFA) production were measured on d 9-12. Protozoa counts were determined at d 9, 11, 13 and 15 and particle-associated bacteria (PAB) from d 13-15. Select bacterial populations in the PAB were measured using RT-qPCR. Fermenter was considered the experimental unit and day of sampling as a repeated measure. Increasing the proportion of bison inoculum resulted in a quadratic effect (P<0.05) on straw, concentrate and total true DM disappearance and on straw and total neutral detergent fibre (aNDF) disappearance, with greater disappearances observed with mixed inoculum. There were no effect of source or proportion of inoculum on ADF disappearance (P>0.05). Increasing bison inoculum linearly increased (P<0.05) concentrate aNDF disappearance, total and concentrate N disappearance as well as total daily VFA and acetate production. A positive quadratic response (P<0.05) was observed for daily NH3-N, propionate, butyrate, valerate, isovalerate and isobutyrate production, as well as the acetate:propionate ratio. Increasing the proportion of bison inoculum linearly increased (P<0.05) total protozoa numbers. No effects were observed on pH, total gas and methane production, microbial N synthesis, or copies of 16S rRNA associated with total bacteria, Selenomonas ruminantium or Prevotella bryantii. Increasing bison inoculum had a quadratic effect (P<0.05) on Fibrobacter succinogenes, and tended to linearly (P<0.10) increase Ruminococcus flavefaciens and decrease (P<0.05) Ruminococcus albus copy numbers. In conclusion, bison inoculum increased the degradation of feed protein and fibre. A mixture of cattle and bison rumen inoculum acted synergistically, increasing the DM and aNDF disappearance of barley straw.